1989
DOI: 10.3109/08990228909144680
|View full text |Cite
|
Sign up to set email alerts
|

Somatotopy of Digital Nerve Projections to the Cuneate Nucleus in the Monkey

Abstract: Somatotopic arrangements of cells and fibers within the dorsal columns and the dorsal column nuclei have been mapped most precisely by electrophysiological recording methods. This study uses an anatomical approach to evaluate the precision of individual digital nerve projections to the cuneate nucleus (CN) in young macaque monkeys. Digital nerves supplying about one-half the palmar skin of a digit were surgically exposed, cut, and treated with wheatgerm agglutinin conjugated to horseradish peroxidase (WGA:HRP)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
23
0

Year Published

1991
1991
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 28 publications
0
23
0
Order By: Relevance
“…However, more recent primate studies showed that neuronal responses due to stimulation of the excitatory receptive field is modulated with stimulation elsewhere on the hand (Friedman et al, 2008; Reed et al, 2008, 2010, 2011, 2012; Thakur et al, 2012). The point-to-point precision of the multisynaptic connections that link cutaneous receptors in the hand with neurons in the hand representation of area 3b (Jones et al, 1982; Culberson and Brushart, 1989; Florence et al, 1989, 1991; Qi et al, 2011) precludes the possibility that this pathway is involved in such widespread activation. We hypothesized that cortical connections to area 3b may reconcile the seemingly contradictory neurophysiological and neuroanatomical observations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, more recent primate studies showed that neuronal responses due to stimulation of the excitatory receptive field is modulated with stimulation elsewhere on the hand (Friedman et al, 2008; Reed et al, 2008, 2010, 2011, 2012; Thakur et al, 2012). The point-to-point precision of the multisynaptic connections that link cutaneous receptors in the hand with neurons in the hand representation of area 3b (Jones et al, 1982; Culberson and Brushart, 1989; Florence et al, 1989, 1991; Qi et al, 2011) precludes the possibility that this pathway is involved in such widespread activation. We hypothesized that cortical connections to area 3b may reconcile the seemingly contradictory neurophysiological and neuroanatomical observations.…”
Section: Discussionmentioning
confidence: 99%
“…Neurons involved in the early stages of sensory processing up to primary somatosensory cortex (area 3b) tend to have small receptive fields that are specific to a limited part of the hand, such as part of a single phalange of a digit (Merzenich et al, 1978; Nelson et al, 1980; Sur et al, 1980, 1985; Pons et al, 1987b; DiCarlo et al, 1998; Xu and Wall, 1999; Zhang et al, 2001). These excitatory receptive fields are mediated by orderly and restricted feedforward connections so that a precise somatotopy exists in the cuneate nucleus of the lower brainstem, the ventroposterior nucleus (VP) of the thalamus, and primary somatosensory area 3b (Merzenich et al, 1978; Kaas et al, 1979, 1984; Jones et al, 1982; Culberson and Brushart, 1989; Florence et al, 1989; Kaas, 1993; Jones, 2007). In monkeys, groups of cells that represent a single digit, or part of a digit, are isolated from each other by surrounding or separating cell-poor septa (Jain et al, 1998b; Rausell and Jones, 1991; Qi and Kaas, 2004; Qi et al, 2011).…”
mentioning
confidence: 99%
“…Neurons responding to stimulation of the lower jaw and neck region have never been reported in V PM (Jones et al, 1986a;Rausell and Jones, 1991a); V PM receives only trigeminal inputs which do not overlap into V PL (Jones et al, 1986b;Rausell and Jones, 1991b). Studies of somatotopy in the dorsal column and principal trigeminal nuclei of monkeys (Kerr et al, 1968;Ferrington et al, 1988;Culbertson and Brushart, 1989;Florence et al, 1989) have not reported whether lower jaw and neck representations are found in both nuclei. There is, however, extensive overlap of upper cervical and trigeminal inputs in the caudal spinal trigeminal nucleus (Kerr, 1972).…”
Section: Intrinsic Connections Of Hand Lower Jaw/neck and Face Reprmentioning
confidence: 99%
“…Primary afferent projections to the dorsal column nuclei from the single peripheral nerve, dorsal root ganglion or muscle, or from a discrete area of the skin have been demonstrated by the transganglionic transport of tracer in the cat (Nyberg andBlomqvist, 1982, 1984;Abrahams et al, 1984;Bakker et al, 1984;Jasmin et al, 1985;Kuo and de Groat, 1985;Robertson and Grant, 1985;Abrahams and Swett, 1986;Mense and Craig, 1988;Nyberg, 1988), rat (Grant et al, 1979;Beck, 1981;Yamamoto et al, 1983;Pfister and Zenker, 1984;Robertson and Grant, 1985;Ueyama et al, 1985;Imamura et al, 1986;Leong and Tan, 1987;Pfaller and Arvidsson, 1988;Neuhuber and Zenker, 1989;Ygge, 1989;Arvidsson and Pfaller, 1990;Maslany et al, 1990Maslany et al, , 1991LaMotte et al, 1991;Rivero-Melian and Arvidsson, 19921, monkey (Edney and Porter, 1986;Florence et al, 1988Florence et al, , 1989Culberson and Brushart, 1989), and guinea pig (Prihoda et al, 1991).…”
mentioning
confidence: 99%